APPLICATION OF THE SAMMAVACA PRINCIPLE TO PROMOTE THE MULTICULTURAL SOCIETY OF SAMNAKTAEO SUB-DISTRICT COMMUNITY, SADAO DISTRICT, SONGKHLA PROVINCE - (Ruangsuwan), Phraathikarn Somsak Thammachoto; ., Phrakru Wijitsilajarn; ., Phrakru Kositwattananukul; ., Phrakru Wichitrarattanawat; ., Phrakru Wateethammawipat (Journal of MCU Nakhondhat, 2024)
The objectives of the study were 1) To study the concept lifestyle in the Multicultural Society of Samnaktaeo Sub-district Community, Sadao District, Songkhla Province, 2) To investigate Sammavaca principle in the Theravada Buddhist scriptures, 3) To apply the Sammavaca in promoting the multicultural society of the Samnaktaeo Sub-district Community, in the life of people in the Samnaktaeo Sub-district Community, Sadao District, Songkhla Province. It is a qualitative research the researcher will survey and collect data through in-depth interviews. The data will be analyzed, summarized, summarized, and presented in a descriptive writing format. Findings were as follows: 1) A multicultural society is a society with a diversity of both races and religions. To live together of the multicultural society of the Samnaktaeo sub-district community is a dependent coexistence and living according to the religious principles that they follow both at the family, community, and social levels, 2) Samavaca means abstaining from false speech ,consisting of four aspects: 2.1) Refraining from telling a lie, speaking truthful words, 2.2) Abstaining from instigating others by inciting two sides of people to break them apart, 2.3) Refraining from speaking harsh words, uttering only sweet words that are pleasant to hear, 2.4) Abstaining blathered speech and speaking only truthful words, 3) The application of the principle of Sammavaca in promoting a multicultural society in the community of Samnaktaeo Subdistrict, Sadao District, Songkhla Province are applied at the family, community and social levels. Verbal statement is the beginning of human relationship. If right and proper words are uttered, it will create love and harmony at all levels; family, community, society, and people can coexist peacefully in a multicultural society.